Isolation of Haemophilus parasuis from Diagnostic Samples in the South of Brazil - Teixeira, Mario L.; Kuchiishi, Suzana S.; Brandelli, Adriano (Brazilian Journal of Veterinary Pathology, 2011)
Haemophilus parasuis is one of the first and most prevalent colonizers of piglets, affecting the swine population from 2 weeks to 4 months of age. In this work, the relative incidence of H. parasuis isolated from swine in the west of Santa Catarina from 2007 to 2010 was investigated. White, flat and non-hemolytic colonies (satellitism growth with Staphylococcus aureus) of approximately 1 mm in length were identified by biochemical tests. Out of 384 samples examined during this period, 32 (8.33%) tested positive to isolation of H. parasuis. In 2007 and 2008 only 1 case of H. parasuis was isolated per year from a total of 62 and 60 samples, respectively. In 2009, 19 cases from 126 (15.08%) and in 2010, 11 cases of H. parasuis were isolated from a total of 136 samples (8.09%). These results suggest a growing incidence of this bacterium in the swine flock in this area.